Markov-switching and the Ifo business climate: The Ifo business cycle traffic lights - Klaus Abberger; Wolfgang Nierhaus (Center for Economic Studies and ifo Institute (CESifo), 2010)
Business cycle indicators are used to assess the economic situation of countries or regions. They are closely watched by the public, but are not easy to interpret. Does a current movement of the indicator signal a turning point or not? With the help of Markov Switching Models movements of indicators can be transformed in probability statements. In this article, the most important leading indicator of the German business cycle, the Ifo Business Climate, is described by a Markov Switching Model. Real-time probabilities for the current business-cycle regime are derived and presented in an innovative way: as the Ifo traffic lights.
Keywords: E32; C22; 330; Ifo business climate; growth cycle; turning points; Markov-switching; Geschäftsklima; Zeitreihenanalyse; Konjunkturumfrage; Markovscher Prozess; Deutschland